THE MASTERY OF ENGLISH VOCABULARY ON FOOD AND DRINK BY THE 4th GRADE STUDENTS OF BUNGA ELEMENTARY SCHOOL SIDOARJO - Sarmi, Ni Nyoman; Putra, Gunadi (Dinamika : Jurnal Sastra dan Budaya, 2016)
This article aimed to find out the vocabulary mastery on food and drink by the 4th Grade students of Bunga Elementary School, Sidoarjo. This thesis uses quantitative research because it is focused on number and analyzing data. The thesis writer uses written test to gather the data from the 4th grade students of Bunga Elementary School, Sidoarjo. After conducting, the thesis writer takes the student’s test paper to analyze how far the students have mastered vocabulary of food and drink. The test consists of 36 Items, divided into three parts. Part 1 is pictures matching, part 2 is blanks filling, and part 3 is essay. Each part has 12 numbers of questions with pictures of food and drink. The thesis writer finds that there are 9 students participate on the test. There are 1 student who gets B+(11.11%), 2 students who get B (22.22%), 1 students who get C (11.11%), 4 students who get D (44.44%), and 1student who gets E (11.11%). It can be concluded that there are 4 students who pass the test and 5 students who fail in mastering vocabulary. He hopes that this thesis could be a guide for teachers and students to improve theirvocabulary.Keywords: vocabulary, mastery, ability